REVIEW POTENSI TANAMAN OBAT AKAR WANGI (Vetiveria Zizanioides) SEBAGAI TANAMAN HIPERAKUMULATOR DALAM FITOREMIDIASI PADA LAHAN TERCEMAR LOGAM - Dwityaningsih, Rosita; Pramita, Ayu; Syarafina, Sumayya (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2019)
Increased population growth results in increasing human needs over time. Meeting the high needs triggered the development of industries that meet the needs. Problems arise from the many industries that emerge, one of which is an environmental problem. Many industries in Indonesia have not used good waste treatment standards, causing pollution from the rest of the production process in the industry, one of which contains heavy metals such as Pb, Zn, Mercury and so on. Heavy metal is a type of pollutant that is harmful to plants, animals and humans through the process of bioaccumulation in the food chain. The purpose of this research is the content of heavy metals that are harmful to the sustainability of ecosystems in the environment requires a long time so that one way to prevent heavy metal compounds that can be released to the environment is by managing the bioremediasi process with fragrant root medicinal plants (Vetiveria Zizanioides) which has hyperaccumulator properties which can absorb one of the heavy metals namely Cadmium (Cd) and Lead (Pb).